PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PENYULUH AGAMA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA KANTOR KEMENTERIAN AGAMA KABUPATEN TAPIN - Zahiya Zahiya; Anthonius Junianto Karsudjono (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2025)
This research reveals that organizational culture and work discipline have a significant influence on organizational commitment in the Ministry of Religion of Tapin Regency. The findings show that improvements in organizational culture can increase the level of organizational commitment, while improvements in work discipline also contribute to increased organizational commitment. However, in the context of religious instructors' performance, although work discipline has a significant positive impact, organizational culture does not significantly influence their performance. On the other hand, a high level of organizational commitment is positively related to increased performance of religious instructors. These results provide a deep understanding of the importance of strengthening organizational culture and improving work discipline to advance organizational commitment and individual performance in the Ministry of Religion of Tapin Regency. The managerial implications of this research include the development of policies that strengthen positive organizational culture and the enhancement of strategies to improve work discipline as an effort to maximize the commitment and performance of religious instructors in this institution